The NuRD chromatin-remodeling complex enzyme CHD4 prevents hypoxia-induced endothelial Ripk3 transcription and murine embryonic vascular rupture - Colijn, Sarah (Cell Death Differ, 2019)
Physiological hypoxia can trigger transcriptional events that influence many developmental processes during mammalian embryogenesis. One way that hypoxia affects transcription is by engaging chromatin-remodeling complexes. We now report that chromodomain helicase DNA binding protein 4 (CHD4), an enzyme belonging to the nucleosome remodeling and deacetylase (NuRD) chromatin-remodeling complex, is required for transcriptional repression of the receptor-interacting protein kinase 3 (Ripk3)—a critical executor of the necroptosis cell death program—in hypoxic murine embryonic endothelial cells. Genetic deletion of Chd4 in murine embryonic endothelial cells in vivo results in upregulation of Ripk3 transcripts and protein prior to vascular rupture and lethality at midgestation, and concomitant deletion of Ripk3 partially rescues these phenotypes. In addition, CHD4 binds to and prevents acetylation of the Ripk3 promoter in cultured endothelial cells grown under hypoxic conditions to prevent excessive Ripk3 transcription. These data demonstrate that excessive RIPK3 is detrimental to embryonic vascular integrity and indicate that CHD4 suppresses Ripk3 transcription when the embryonic environment is particularly hypoxic prior to the establishment of fetal-placental circulation at midgestation. Altogether, this research provides new insights into regulators of Ripk3 transcription and encourages future studies into the mechanism by which excessive RIPK3 damages embryonic blood vessels.